Application of Islamic Educational Philosophy in Holistic and Contextual Curriculum Design: An Integrative and Humanistic Approach - Asykur, Muamar; Hidayat, Muhammad Taufiqul; Fauza, Zhalfa Luthfi; Oktianto, Dwi Cahya (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This article discusses how Islamic educational philosophy can be the foundation for designing a holistic and contextual curriculum through an integrative and humanistic approach. In facing the challenges of contemporary education that tends to be fragmented and oriented solely to academic achievement, this approach offers a comprehensive solution by touching on all dimensions of students' humanity, spiritual, intellectual, emotional, and social. This study uses a descriptive qualitative research method based on literature studies, by reviewing relevant scientific literature in the last five years. The results of the study show that Islamic educational philosophy through ontological, epistemological, and axiological foundations places students as active subjects in the educational process that unites faith, knowledge, and charity. The holistic curriculum is designed to develop the potential of students as a whole, while the contextual curriculum links learning to the reality of life. The integrative approach avoids the dichotomy between religious knowledge and general knowledge, while the humanistic approach encourages recognition of the dignity and unique potential of each student. The implications of designing a curriculum based on this philosophy are seen in the learning pattern, the role of the teacher as a murabbi, and the evaluation model that touches on the affective and spiritual aspects. However, its implementation still faces challenges, such as limited teacher competency, inflexible curriculum structure, and lack of supporting facilities. Therefore, synergy is needed between policy makers, educators, and the community to realize Islamic education that is holistic, contextual, and meaningful spiritually and socially.